On the Measurement of Change in Medical Research - Luiz, Ronir Raggio; Almeida, Renan Moritz V.R. (International Journal of Statistics in Medical Research, 2012)
Measuring of change is essential in medical research. However, these measurements may have different goals and, traditionally, the ability to measure change has focused on sensitivity in a statistical sense, whereas little attention has been directed to the appropriate interpretation and analysis of change indicators. The present report examines some of the most important issues involved in measuring change with pre and post-test data when ordinal scales are used, and the conceptual problems pertaining to the use of these scales are also discussed. It can be said that there is still no agreement about the most adequate strategy for assessing health status change in a group of subjects, what caused the introduction of many indicators, most of which variations of the ES (Effect size: the mean of change scores divided by the standard deviation of the baseline scores) concept. The adequate interpretation of change scores in these cases demands a high degree of knowledge about what these changes mean to specific sub-groups of patients, as well as detailed information on their situation at baseline, such as score distributions. Researchers should strive for interpretations that take into account what "change" means for different patients.